Determining the quality of life of children living with epilepsy in Kenya—A cross-sectional study using the CHEQOL-25 tool. (March 2020) - Hussain, Syeda Ra'ana; Orwa, James; Sokhi, Dilraj Singh; Kathomi, Caroline Mbuba; Dossajee, Hussein; Miyanji, Osman; Ngugi, Anthony; Samia, Pauline
Highlights: Most tools measuring quality of life (QoL) rely on parent/caregiver feedback rather than the child's perspective. CHEQOL-25 is a QoL tool that documents both child and caregiver perspectives across five domains. QoL was reported as good by both CWE and their caregivers in the majority of our cohort.. QoL was lower if caregiver for CWE was male or less educated. Abstract: Purpose: Epilepsy is a chronic neurological disorder that is often diagnosed in childhood and may negatively impact physical, social and psychological abilities. Most tools measuring quality of life (QoL) rely on parent/caregiver feedback rather than the child's perspective. CHEQOL-25 is a QoL tool that documents both child and caregiver perspectives across five domains. The primary objective was to determine the QoL of children living with epilepsy (CWE) using the CHEQOL-25 tool in a Kenyan paediatric population. Other objectives were to describe the correlation between the caregivers' and children's' perspectives and describe factors affecting QoL. Method: We conducted a cross-sectional study across four sites in Nairobi. Quantitative data was collected using a self-administered CHEQOL-25 questionnaire. Caregivers and their children aged 7–15 years attending neurology clinics participated in the study. We used Kappa statistics to compare child and caregiver responses. Results: A total of 354 participants were interviewed (177 children and 177 caregivers). A good QoL was reported by 60.5 % of children with a similar caregiver perception of 56.5 %. Caregivers with little education and male caregivers were associated with a poor QoL (p = 0.01); other socio-demographic factors had little impact on the measured QoL of CWE. Parent and child questionnaires correlated well in terms of response in terms of interpersonal (p = 0.001) and intrapersonal (p = 0.004) domains. Conclusion: This study demonstrated that a good quality of life was reported by the majority of CWE and their caregivers, although some factors such as a male caregiver gender and lower level of education were associated with poor QoL.